Release of beryllium from mineral ores in artificial lung and skin surface fluids - Duling, Matthew G.; Stefaniak, Aleksandr B.; Lawrence, Robert B.; Chipera, Steve J.; Abbas Virji, M. (Environmental geochemistry and health, 2012)
Exposure to some manufactured beryllium compounds via skin contact or inhalation can cause sensitization. A portion of sensitized persons who inhale beryllium may develop chronic beryllium disease (CBD). Little is understood about exposures to naturally occurring beryllium minerals. The purpose of this study was to assess the bioaccessibility of beryllium from bertrandite ore. Dissolution of bertrandite from two mine pits (Monitor and Blue Chalk) was evaluated for both the dermal and inhalation exposure pathways by determining bioaccessibility in artificial sweat (pH 5.3 and pH 6.5), airway lining fluid (SUF, pH 7.3), and alveolar macrophage phagolysosomal fluid (PSF, pH 4.5). Significantly more beryllium was released from Monitor pit ore than Blue Chalk pit ore in artificial sweat buffered to pH 5.3 (0.88 ± 0.01% vs. 0.36 ± 0.00%) and pH 6.5 (0.09 ± 0.00% vs. 0.03 ± 0.01%). Rates of beryllium released from the ores in artificial sweat were faster than previously measured for manufactured forms of beryllium (e.g., beryllium oxide), known to induce sensitization in mice. In SUF, levels of beryllium were below the analytical limit of detection. In PSF, beryllium dissolution was biphasic (initial rapid diffusion followed by latter slower surface reactions). During the latter phase, dissolution half-times were 1,400 to 2,000 days, and rate constants were ~7 × 10 −10 g/(cm 2 ·day), indicating that bertrandite is persistent in the lung. These data indicate that it is prudent to control skin and inhalation exposures to bertrandite dusts.